2009
DOI: 10.1149/1.3216029
|View full text |Cite
|
Sign up to set email alerts
|

Charge Density in Atmospheric Pressure Chemical Vapor Deposition TiO[sub 2] on SiO[sub 2]-Passivated Silicon

Abstract: The charge density of a TiO2 film deposited on a SiO2 -passivated silicon wafer is determined. The TiO2 is deposited by atmospheric pressure chemical vapor deposition at 400°C , and the SiO2 is grown thermally at 950°C . This TiO2–SiO2 stack is a useful coating for the front surface of a silicon solar cell, as it has a high optical transmission and a low density of interface states Dit(E) at the SiO2–Si interface. While these properties are beneficial to high efficiency solar cells, so too is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…The value E 0 takes has been previously suggested to be near the mid-gap. 36,56 Simulations conducted in Section III showed that a value of neutral energy E 0 in the range ÀE g =4 < E 0 < þE g =4 had a negligible effect on SRV, as can also be inferred from Girisch's treatment, 15 and thus, a value E 0 ¼ E g =2 is assumed throughout this work. In general, changes in the dielectric fixed charge can produce changes in both donor and acceptor states at the interface.…”
Section: F the Effect Of Interface Charge Concentrationmentioning
confidence: 89%
See 2 more Smart Citations
“…The value E 0 takes has been previously suggested to be near the mid-gap. 36,56 Simulations conducted in Section III showed that a value of neutral energy E 0 in the range ÀE g =4 < E 0 < þE g =4 had a negligible effect on SRV, as can also be inferred from Girisch's treatment, 15 and thus, a value E 0 ¼ E g =2 is assumed throughout this work. In general, changes in the dielectric fixed charge can produce changes in both donor and acceptor states at the interface.…”
Section: F the Effect Of Interface Charge Concentrationmentioning
confidence: 89%
“…Although D it;q has been typically described by an inverse Gaussian function, additional extensions have been proposed by adding exponential tail functions to model the high density of states near the band edges. 20,56 Despite the high density of such near band tail states, they contribute negligibly to the recombination activity at the surface. This is a consequence of the extended SRH process as described in Section II E. In this work, a three term exponential function is proposed to model D it;q .…”
Section: F the Effect Of Interface Charge Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The degradation of the material after 325 cycles reported in Figure 50 was evaluated with the SKP, as shown in Figure 53 A charge injection technique is commonly used to determine the integrity of gate oxides in semiconductor fabrication by depositing charge through a corona discharge [165]. If the trapped charge is located within the polymer layer and is significantly larger than the native charge in the aluminum oxide and interface, the charge density is simply given by the potential drop due to the capacitance of the polymer [166], [167]. Under this assumption, the charge derived from the CPD values is estimated to be 5.…”
Section: Cyclic Electrowettingmentioning
confidence: 99%
“…Using the charge density interpretation from the corona charge measurements, the charge density is only given through the potential drop due to the capacitance of the polymer [166], [167]. This suggests that the observed value of charge for zero contact angle change is independent of the underlying oxide layer.…”
Section: Cyclic Electrowettingmentioning
confidence: 99%